The Perplex of Deforestation in sub-Saharan Africa - Yalew, A.W. (Department of Forestry and Environmental Science University of Sri Jayewardenepura, 2015)
Deforestation has been a complex phenomenon to study in sub-Saharan Africa. The average annual deforestation rate in the region is by far higher than the world average. What causes and drives deforestation in the region are debated to date. The present paper is motivated by this debate. It attempts to test whether the maintained hypotheses on the causes of deforestation can give answer to the problem in sub-Saharan Africa. It used average cross-national data of forty eight countries in the region. The data are retrieved from international sources. The Spearman’s rank correlation coefficients between two deforestation indicators and five often-cited causes of deforestation were computed. The role of public forest ownership, share of forest and agricultural products in total exports, and the year of forest laws enacted are also discussed. However, it finds no clear, strong, and systematic pattern to argue that population density, rural population, rural poverty, industrial logging for exports, economic growth, late enactment of forest laws, and public ownership of forests are underlying causes of deforestation in the region. The trends of forestland in Rwanda and Zimbabwe vividly present the finding. Therefore, future studies related to the topic in the region shall focus on sub-national panel data.
Keywords: deforestation, population, economy, institutions, sub-Saharan Africa